Mobile Technologies and Digitized Data to Promote Access to Finance for Women in Agriculture - World Bank Group (World Bank, Washington, DC, 2017)
The evidence that women both drive agricultural production and rely on it for their livelihoods means that greater financial and informational service provision to women, especially through digital channels, could increase the efficiency and effectiveness of their labor. While the numerous barriers to women’s access to Digital financial Services (DFS) are clear, clarifying the best methodologies by which to overcome these is both dependent on situational context and still subject to research and testing. This report provides the state of play of current and promising efforts that use mobile technology and digitized data to close the gap in access to finance for women in agriculture. It includes three components: 1) a review of the financial characteristics and needs of women in agriculture, based on an extensive literature review; 2) a stock taking of initiatives that use mobile technologies and digitized data for agricultural finance and women’s financial inclusion; and 3) an analysis of gaps in existing initiatives that would increase access to DFS by women farmers, laborers and women-owned agricultural MSMEs. The report also examines the regulatory environment around DFS and ways that regulators are working to increase responsible access to women.